2011
DOI: 10.1007/s10620-011-1850-4
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Gastric Ulcer Healing After Endoscopic Submucosal Dissection Including the Promoting Effect of Rebamipide

Abstract: Healing in ESD-induced ulcers was dependent on the initial ulcer size. In large-sized ulcers, rebamipide promotes basal healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
(32 reference statements)
4
47
1
1
Order By: Relevance
“…We found that large artificial ulcers and location of the lesion in the lower third of the gastric tract to be independent risk factors of delayed post-ESD ulcer healing. Our finding of delayed healing of large artificial ulcers is consistent with the results of Kobayashi et al [9] and Oh et al [10]. Size of artificial ulcer after ESD has also been reported to affect the healing rate of artificial ulcers in previous studies [9,10,14], supporting our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that large artificial ulcers and location of the lesion in the lower third of the gastric tract to be independent risk factors of delayed post-ESD ulcer healing. Our finding of delayed healing of large artificial ulcers is consistent with the results of Kobayashi et al [9] and Oh et al [10]. Size of artificial ulcer after ESD has also been reported to affect the healing rate of artificial ulcers in previous studies [9,10,14], supporting our findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is no current consensus regarding the optimal duration of PPI or P-CAB treatment after ESD based on the various factors that can influence healing of post-ESD ulcers. Potential predictive factors of delayed ulcer healing include the large size of artificial ulcers [9,10], the use of H2RA after ESD [5,6], preoperative fibrosis in the submucosal layer of the lesions [3], damage to the muscularis propria layer during the ESD procedure [11], location of the resected lesion in the lesser curvature [12], and lesions combined with severe atrophic gastritis [13]. However, these risk factors were identified prior to the release of P-CABs and, therefore, these studies did not consider P-CAB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A synergic effect with another approach, such as a shielding method [16], is necessary. Several studies have targeted post-ESD ulcer healing as a primary end point by using antisecretory agents and/or mucoprotective agents [23][24][25][26][27]. These studies clearly elucidated the difference between peptic ulcer and artificial post-ESD ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Takayama et al [23] revealed that 1 week of PPI treatment followed by 7 weeks of rebamipide treatment had effects similar to those of 8 weeks of PPI treatment with regard to post-ESD ulcer healing. Kobayashi et al [24] compared 8 weeks of treatment with a PPI alone and 8 weeks of treatment with a PPI plus rebamipide. Although ulcer healing was evaluated 4-6 weeks after ESD, the healing ratio with regard to scar stage was similar in both groups, but the quality of basal healing was significantly better in the combination group among patients with large resection in the subanalysis.…”
Section: Complications and Their Preventionmentioning
confidence: 99%
“…In randomized controlled studies, rebamipide has been found to prevent nonsteroidal anti-inflammatory drug (NSAID)-induced peptic ulcers, accelerate gastric ulcer healing and suppress mucosal inflammation in patients with chronic erosive gastritis (6,7). Recently, several studies (8)(9)(10)(11)(12)(13)(14) have examined the efficacy of rebamipide and PPI combination therapy for the treatment of ESD-induced ulcers. However, there is currently no consensus regarding the optimal treatment duration or drug regimen.…”
Section: Introductionmentioning
confidence: 99%